STRATEGI OFFLINE MARKETING UMKM MINIATUR KAPAL DESA PENGUDANG DALAM MENINGKATKAN MINAT KONSUMEN - Herman, Herman; Saputra, Eko Murti; Mu’azamsyah, Muhammad; Nazila, Hiexmanatun; Kelvin, Kelvin; Syafitri, Ramdani; Sulistianingsih, Ranti; Rinanda, Sevina; Elsa, Umi (Jurnal Pengabdian, Pembelajaran dan Pemberdayaan Ekonomi Masyarakat (JP3EM), 2025)
Offline marketing is a direct selling method, in which marketers or manufacturers approach customers directly with the products and services offered. The purpose of this research is to find out what strategies are being carried out in offline marketing for micro-miniature Pinisi ships in Pengundang village in increasing consumer interest. the method used is a qualitative research method with a descriptive analysis approach. data obtained from interview documentation. The results of this study indicate that the result of offline marketing for the miniature Pinisi ship SMEs is that they can market the miniature ships through brochures, business cards as the identity of the UMKM which makes it easier if anyone wants to order the miniature. Apart from that, nameplates are also installed on the side of the road so that it has an impact on making it easier to find the public address of the miniature Pinisi ship, which will attract tourists or other consumers as souvenirs while in Pengudang Village.